Supply Chain Management, Firm Size and Intellectual Capital Models to Predict Capital Structure and Profitability in the Manufacturing Industry - Chandra, Stefani; Wijaya, Evelyn; Panjaitan, Harry P.; Hafni, Layla; Chandra, Jennifer (International Journal of Supply Chain Management, 2020)
Abstract- The implementation of supply chain management is necessary to support a company’s operational activities especially in the manufacturing industry. Capital structure is part of the supply chain strategy that plays an important role in funding decision making in effort to boost company profitability. This study aims to analyze the effect that supply chain management, firm size and intellectual capital have on the capital structure and profitability in the manufacturing industry. The population in this study was all manufacturing industries registered in the Indonesia Stock Exchange (BEI) of 145 companies. 96 companies from the period 2010-2018 were taken as the sample using the purposive sampling technique. Data in this study were analyzed using path analysis with AMOS software. The results showed that supply chain management dan firm size had no significant effect on capital structure and profitability, while intellectual capital negatively affected capital structure but had a significant positive effect on profitability, and capital structure had a significant negative effect on profitability. The results are in agreement with the pecking order theory stating that a company capable of gaining high profits tends to have low corporate debt.